2019
DOI: 10.3389/fpsyg.2019.01691
|View full text |Cite
|
Sign up to set email alerts
|

Bullied Adolescent’s Life Satisfaction: Personal Competencies and School Climate as Protective Factors

Abstract: Although adolescence has been defined as a stage of vulnerability, due to the biopsychosocial changes that happen throughout this developmental stage, it is also one of growth. Some of the core personal competencies that have been identified to promote positive development at this stage while simultaneously preventing risks are: (1) a positive sense of self, (2) self-regulation, (3) decision-making skills, (4) a moral system of belief, and (5) prosocial connectedness. There are many factors and contexts that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 91 publications
(114 reference statements)
4
26
1
7
Order By: Relevance
“…satisfaction (Lázaro-Visa et al, 2019;Ramos-Díaz et al, 2019) and life satisfaction negatively predict delinquency (Jung and Choi, 2017;Hanniball et al, 2018). In the separate regression analysis, all related PYD attributes also showed significant direct predictions on delinquency.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…satisfaction (Lázaro-Visa et al, 2019;Ramos-Díaz et al, 2019) and life satisfaction negatively predict delinquency (Jung and Choi, 2017;Hanniball et al, 2018). In the separate regression analysis, all related PYD attributes also showed significant direct predictions on delinquency.…”
Section: Discussionmentioning
confidence: 86%
“…The above theoretical notions have been supported by rich empirical findings showing positive predictions of PYD attributes on adolescent life satisfaction (Zhang, 2016;Lázaro-Visa et al, 2019;Ma, 2020) and negative predictions of life satisfaction on adolescent delinquency (Jung and Choi, 2017;Hanniball et al, 2018;Lee et al, 2020). A handful of pioneering studies have empirically tested the mediational role of life satisfaction in linking PYD attributes to behavioral problems (Sun andShek, 2010, 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first strategy was to perform hierarchical multiple regression analyses based on ordinary least square (OLS) approach to examine the prediction of a PYD variable (e.g., positive identity composite scores) on an outcome (e.g., life satisfaction), with the predictors entered in blocks (e.g., control variables in Block 1 and Wave 1 PYD variable in Block 2). In the literature on longitudinal studies, researchers have commonly used this approach ( Steinberg et al, 1989 ; Davis et al, 2019 ; Lázaro-Visa et al, 2019 ). We used SPSS 25.0 to conduct the multiple regression analyses as well as attrition and reliability analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, low self-esteem facilitates implication in criminal conducts or other risk conducts such as consumption and would highlight the importance of other variables, such as the family, academic, and social context. Thus, Christens and Peterson (2012) found that greater social support in the family, among peers, and also in the academic environment increases not only self-esteem but also the protective factors for violent conducts (Lázaro-Visa et al, 2019) and substance consumption (Malonda et al, 2019).…”
Section: Introductionmentioning
confidence: 98%